Selected poems - Stampa, Gaspara, approximately 1523-approximately 1554 (Italica Press, 1994)
"Gaspara Stampa (1523-54) is considered the greatest woman poet of the Italian Renaissance, and she is regarded by many as the greatest Italian woman poet of any age. A highly skilled musician, Stampa produced some of the most musical poetry in the Italian language. Her sonnets of unrequited love speak in a language of honest passion and profound loss. They look forward to the women writers of the nineteenth century and are a milestone in women's literature. This dual-language edition of selected poems presents, along with the Italian original, the first English translation of Stampa's work. It includes an introduction to the poet and her work, a note on the translation, and provides the reader with notes to the poems, a bibliography, and a first-line index."--Book cover, page [4]